Dialogcal Framing: A Content Analysis of National Online Media Coverage on the â€œIndonesia Gelapâ€ Issue in 2025 - Agus Priyanto; Sarah Ayu Putri Novaria; Husnaeni Fauziah Amani (Nyimak: Journal of Communication, 2026)
Online media play a strategic role in shaping public opinion in the digital era through mechanisms of information framing. This study aims to examine how Indonesian online media frame the controversial issue of â€œIndonesia Gelapâ€. Employing a descriptive qualitative approach, this research applies Robert Entmanâ€™s framing analysis model to systematically dissect media texts. The data were drawn from selected news articles chosen purposively from five leading mainstream online media outlets with the highest readership Detik.com, Kompas, CNN Indonesia, Liputan6, and Tempo. Data analysis was conducted systematically with the assistance of NVivo software to enhance the rigor and transparency of the coding process. The findings reveal that despite the crisis-laden connotation embedded in the phrase â€œIndonesia Gelap,â€ the dominant narrative constructed by the media is dialogical rather than confrontational. The media do not merely amplify negative aspects of the issue; instead, they highlight the governmentâ€™s proactive responses in opening deliberative spaces for public discussion. This study addresses a research gap by demonstrating that, within the context of Indonesiaâ€™s digital democracy, online media can function as dialogical mediators rather than merely as agents of polarization. For scholars and readers, these findings offer a new analytical perspective in political communication studies, particularly in understanding how media frame governmental responses to issues that have the potential to shape dialogical discourse within the digital public sphere.Keywords: Media narrative, government communication, media framing, public policy, digital media practicesÂ ABSTRAKMedia online memiliki peran strategis dalam membentuk opini publik di era digital melalui mekanisme pembingkaian informasi. Penelitian ini bertujuan untuk mengkaji bagaimana media online di Indonesia membingkai isu kontroversial "Indonesia Gelap". Menggunakan pendekatan kualitatif deskriptif, penelitian ini menerapkan analisis framing model Robert Entman yang membedah teks. Data bersumber dari beberapa artikel yang dipilih secara purposive dari lima media arus utama dengan pembaca terbanyak (Detik.com, Kompas, CNN Indonesia, Liputan6, dan Tempo). Pemilihan artikel kunci ini dianggap representatif karena berasal dari market leader media daring yang menjadi rujukan utama narasi nasional di Indonesia, sehingga mampu mencerminkan tren opini publik secara luas. Analisis data dilakukan secara sistematis dengan bantuan perangkat lunak NVivo untuk menjaga objektivitas pengodean. Hasil penelitian menunjukkan bahwa di balik diksi "Indonesia Gelap" yang bernuansa krisis, narasi dominan yang muncul justru bersifat dialogis. Media tidak hanya mengeksploitasi aspek negatif, tetapi juga menyoroti respons proaktif pemerintah dalam membuka ruang diskusi deliberatif dengan masyarakat. Temuan ini mengisi celah penelitian (research gap) dengan menunjukkan bahwa dalam konteks demokrasi digital di Indonesia, media dapat berfungsi sebagai mediator dialogis ketimbang sekadar agen polarisasi. Bagi pembaca, studi ini memberikan kontribusi penting mengenai bagaimana narasi krisis di negara berkembang dapat diredam melalui strategi komunikasi publik yang inklusif, menawarkan perspektif baru dalam studi komunikasi politik.Kata Kunci: Narasi media, komunikasi pemerintah, pembingkaian media, kebijakan publik, praktik media digital